Regional dimensions of infant mortality rate in Brazil, 1980-2000 - Ana Barufi; Eduardo Haddad; Antonio Paez (European Regional Science Association (ERSA), 2010)
Development can be understood from many perspectives. Among those, the one proposed by Amartya Sen states that a development policy should aim at expanding the freedom of individuals, and this goal can be achieved by the expansion of capabilities. With this conceptual framework in mind, health, more specifically infant mortality, is chosen as a measure of development and as the object of study. The Government should guarantee the provision of health services, as they consist in meritory goods. Mosley and Chen (1984) propose a theoretical framework to study infant mortality based on the proximal determinants, in which the socioeconomic factors affect the result observed indirectly. In Brazil there has been a substantial reduction of the average levels of infant mortality rates in the last decades. However, there is still a significant regional inequality. Econometric models for 1980, 1991 and 2000 are estimated including a spatial filter in order to account for the spatial dependency observed in the data. The study concludes that health infrastructure lost its explanative power for the differences in infant mortality rate among the localities. On the other hand, socioeconomic variables have become more relevant and significant. It means that future public policies must try to improve the access of the families to public facilities, reduce poverty and inequality and improve educational levels. Therefore, the family-based prevention against health problems should be stimulated, helping to avoid premature death.
Keywords: 330; development; infant mortality; spatial filter